Порівняльна оцінка активованих вугіль в процесах сорбції нафтопродуктів легкої та середньої фракцій - Січевий, Олексій Володимирович; Левицька, Олена Григоріївна; Долженкова, Олена Вікторівна; Золотько, Олена Василівна (НТУ "ХПІ", 2017)
Визначена сорбційна ємність активованих вугіль із переважанням мікро-, мезо- та макропор, виконаних відповідно із шкаралупи кокосового горіху, кам’яновугільного пилу, берези, в процесах сорбції нафтопродуктів легкої та середньої фракцій: бензинів А92, А95, дизельного палива та керосину в динамічних та статичних умовах. Показані залежності сорбційної ємності сорбентів у статичних умовах від часу їх взаємодії із сорбатами та виявлені найвищі значення сорбційної ємності для сорбентів, виконаних із берези.

The sorption capacity of activated carbon with the prevalence of micro-, meso- and macropores respectively made from coconut shell, coal dust, birch in the sorption processes of petroleum products light and medium petroleum fractions: gasoline A92, A95, diesel fuel and kerosene in dynamic and static conditions was determined. The values of sorption capacity of sorbates and the time in which constant values of sorption capacity in static conditions in the interaction of sorbents with different factions oils are set were compared. Dependences of sorption capacity of sorbents in static conditions from the time of their interaction with sorbates were shown and the highest values of sorption capacity were revealed for sorbents made from birch, the lowest values – for sorbents made from coal dust.
Comparative evaluation of activated carbons in sorption processes of petroleum products light and medium fractions
Keywords: сорбент; ємність сорбційна; вугілля активоване; бензин; паливо дизельне; керосин; sorbent; sorption capacity; activated carbon; benzene; diesel fuel; kerosene